Correlation between panoramic radiographic signs and high‐risk anatomical factors for impacted mandibular third molars. (19th February 2013) - Harada, N.; Vasudeva, S.B.; Joshi, R.; Seki, K.; Araki, K.; Matsuda, Y.; Okano, T.
Abstract Aim To determine the relationship between radiographic signs on panoramic radiographs and anatomic features of thinning of the cortical plates and closeness of the root of the third molar to the mandibular canal on cone beam computed tomography images (CBCT). Methods Panoramic images were analysed for the relationship of the root of the third molar to the mandibular canal. The CBCT images were analysed for the relation between mandibular canal and the third molar root. The results were tabulated, and Chi square test (P < 0.05) was used for the assessment of the relationship between the panoramic sign and the CBCT findings. Results The panoramic signs, especially, darkening of the root and interruption of the white line of the canal correlated with the location of the mandibular canal to the impacted tooth, thinning of the lingual cortical plate and the closeness of the canal and the molar. Conclusion Darkening of the root and interruption of the white line of the canal on panoramic radiograph can predict lingual cortical plate thinning and close relation between third molar root and the mandibular canal.